Comparación de dos métodos de sincronización de Celo en Ovinos de la Raza Marin Magellan Meat Merino (4m) en la Provincia de Cotopaxi - Aucanshala Cutuan, Mirian Elizabeth (2019)
The investigation was aimed at comparing the methods of heat synchronization in sheep of the Marin Maguellan Meat Merino sheep (4M) in the genetic nucleus "Yanahurco Grande" in the province of Cotopaxi, through the use of two methods synchronization methods so that their effect on ovarian activity can be determined, which lasted 50 days. Twenty first sheep of the 4M breed were selected, the animals were randomly selected, taking into account the homogeneity of the group. The first heat synchronization protocol was with prostaglandins (PGF2α), which was published as follows: on the first day or zero PGF2α (Cloprostenol, Estrumate) is applied intramuscularly in a dose of 0.5 ml. On day 11 the 0.5 ml dose was repeated, via IM and finally the heat was observed on day 14. The second protocol was performed with the use of progestogens: on day 0 intravaginal devices were placed with progesterone, on day 11 the implants were removed and the 300 IU of eCg (Novormon 5000) was administered intramuscularly and observed on day 14. Statistical analysis was performed using the Chi-square test for qualitative variables: vulde edematization, receptivity of the vulva male, estrous cycle phase; and the ANOVA test for ovarian activity, the numbers of the follicles, the sea in the selection phase and the domain by ultrasound were counted, giving the best and best result to the T1 in which 19 follicles were observed in the phase of dominance, versus T2 Where 9 follicles were observed in the dominance phase. As a result of T1, corresponding to the use of Prostaglandins PGF2α as the best protocol in this study, where 7 sheep of the Marin Magellan Meat Merino breed (7/10 animals) in question heat.